The innovator's discussion : the conversational skills of entrepreneurial teams - Campbell, Betsy, 1966- (London : Routledge, 2019)
This book describes the conversational competencies that enable innovative entrepreneurial teams to create new products and ventures, and it presents several exercises and games to help readers master these conversational moves. Based on6 years of detailed empirical analysis of teams at the forefront of technological breakthroughs and new venture creation, this book shows you how high-performance teams verbally accomplish their work. Through engaging examples, exercises, and descriptions, it enables entrepreneurs to develop the conversational competencies that can help them create new products and ventures. The book includes a technique for making interpretation visible that enables teams to navigate pivots in the innovation process. It also includes the materials and instructions for the Toasted Marshmallow game designed to help entrepreneurial teams fail forward. The Innovator's Discussion enables readers and their team mates to build a conversational advantage. The reader will gain both a practical and theoretical understanding of the role of conversation in the context of entrepreneurial work. It is invaluable for aspiring and established entrepreneurs as well as for educators and those wanting to learn more about entrepreneurship, innovation, and high-performance teams.
OCLC-licensed vendor bibliographic record.
Keywords: Creative ability in business; Teams in the workplace; Communication in management; New products; Technological innovations -- Management; Entrepreneurship; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Entrepreneurship